Analisis Diskursus Feminisme dalam Kebijakan Pemenuhan Hak Pekerja Perempuan di Sektor Informal di Indonesia - Tiffany Setyo Pratiwi; Muhammad Dede Puja Kusuma (Universitas Jabal Ghafur, 2025)
ABSTRACTThis article analyzes the development of feminist discourse in policies to fulfill the rights of women workers in the informal sector in Indonesia. This research examines how gender approaches and women's rights are negotiated by various stakeholders. This research uses a qualitative literature study approach and Norman Fairclough’s critical discourse analysis framework. Text analysis of the Manpower Law Number 13 of 2003 and the Job Creation Law shows that there is no text